Consumer Search and Prices in the Automobile Market - José Luis Moraga-González; Zsolt Sándor; Matthijs R. Wildenbeest (Tinbergen Institute, 2015)
In many markets consumers have imperfect information about the utility they derive from the products that are on offer and need to visit stores to find the product that is the most preferred. This paper develops a discrete-choice model of demand with optimal consumer search. Consumers first choose which products to search; then, once they learn the utility they get from the searched products, they choose which product to buy, if any. The set of products searched is endogenous and consumer specific. Therefore imperfect substitutability across products does not only arise from variation in their characteristics but also from variation in the costs of searching them. We apply the model to the automobile industry. Our search cost estimate is highly significant and indicates that consumers conduct a limited amount of search. Estimates of own- and cross-price elasticities are lower and markups are higher than if we assume consumers have full information.
Keywords: C14; D83; L13; 330; consumer search; differentiated products; demand and supply; automobiles